Optimizing Rice Cultivation: Impact of Mid-Season Drainage, Sulphate and Blue-Green Algae on Yield and Greenhouse Gas Emissions - Natarajan, S. K.; Kavitha Mary, J.; Senthilraja, K.; Usharani, K.S.; Geethalakshmi, V.; Bhuvaneswari, J (Geography, Earth Science and Environment: Research Highlights Vol. 3, 2025)
This study evaluates the effects of mid-season drainage, sulphate addition, and blue-green algae application on methane emissions, carbon flux, and rice yield using field experiments and the DNDC model. Results demonstrated a 48% reduction in methane emissions and significant yield improvements with combined practices. The DNDC model validated these findings, showcasing its utility in estimating greenhouse gas emissions under modified management conditions. These findings highlight the potential for integrating sustainable practices in rice cultivation to mitigate climate change while maintaining productivity.